Black gun, silver star: the life and legend of frontier Marshal Bass Reeves - Burton, Arthur T. (Race and ethnicity in the American West, 2022)
In this new edition of the biography of Bass Reeves, who was formerly enslaved and then served as a peace officer in and around late nineteenth-century Indian Territory, Art Burton traces Reeves's presence in contemporary national media and in popular modern media